Alcohol drinking in male patients with chronic schizophrenia: prevalence and its relationship to clinical symptoms - Lv, Menghan; Wang, Xuan; Wang, Zhiren; Li, Xiaohong; Wang, Li; Tan, Yunlong; Zhang, Xiang Yang (Frontiers in Psychiatry, 2023)
Background It is common practice to associate schizophrenia (SCZ) patients with substance use. The most commonly used substances in China are tobacco and alcohol. However, few studies have focused on alcohol consumption itself in patients with SCZ. Thus the purpose of this study was to detect the prevalence of alcohol use and associated clinical factors in Chinese patients with SCZ. Methods A total of 616 male inpatients who met the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) criteria for SCZ participated in this study. A detailed questionnaire, including data on alcohol consumption was used to collect demographic and clinical information on all patients. The five-factor model of the positive and negative syndrome scale (PANSS) was adopted to assess psychiatric symptoms. Results In this study, 31.49% of SCZ inpatients had a history of alcohol use, and 82.9% of these patients abstained from alcohol use after the onset of SCZ. Compared to nondrinkers, patients who drank were more likely to smoke (p = 0.004), more likely to have suicide attempts (p = 0.002) and suicidal ideation (p = 0.001), more severe positive (p < 0.001) and depressive symptoms (p = 0.034), but less severe negative symptoms (p = 0.04). Conclusion These findings suggest that alcohol use is common during the lifetime of SCZ patients and that alcohol use may be associated with clinical symptoms in SCZ patients.